PENGARUH PEMBANGUNAN PERMUKIMAN MASYARAKAT DAYAK BAWO TERHADAP PERUBAHAN KEBUDAYAANNNYA - Hartatik Hartatik (Balai Arkeologi Kalimantan Selatan, 2010)
The Bawo people reside in the northern part of Meratus Mountain and survive by living a continuous nomadic life roaming from one hill to other until today. The Bawo people preferred to live solitary life instead and practically have no contact with the outside world. Material data on the existence of the Bawo people comprise of ‘keriring’ and ‘raung’ found stored in rock shelters. Through a long process, the Social Departement of the Republic of Indonesia with its population resettlement program had succeeded to provide ideal kampong for them to live in named PMT Malungai. This article discusses how the Bawo people respond to such program and the impact on the Bawo culture in respect with its survival.